Collaborative R&D capabilities: In search of micro-foundations - Line Gry Knudsen (Copenhagen Business School (CBS), 2009)
The aim of this thesis is to improve the understanding of how collaborative R&D capabilities come about and how they are jointly determined by individual and organizational level factors. I argue that despite the fact that a surge of interest in inter-organizational collaboration has been witnessed in research fields as diverse as strategic management, economics, sociology, and organization theory, we know very little about the micro-foundations of collaborative R&D capabilities. Processes going on internally in collaborating firms are treated like a `black box' in many strands of research. How, we may ask, does openness towards external knowledge sources lead to enhanced R&D performance? What are the internal organizational mechanisms that facilitate the collaborative processes? How are specific collaborative capabilities developed to ensure collaborative success, and—most importantly—what is their composition in terms of organizational and individual level factors? In this thesis these and related questions are addressed by means of empirical as well as theoretical analyses. It is argued that studies of strategic alliances and R&D collaborations have suffered from being mainly conducted on large datasets and with little attention to individual level factors that may be key drivers of alliance success. The case-study methodology is emphasized as a useful complementary method as it entails the option of learning from the employees engaged in the formation and operation of collaborative arrangements. Three narrative studies are undertaken with the aim of identifying the micro-foundations of collaborative R&D capability in the firms. This is done to provide an explorative overview of the determinants rather than to evaluate the degree to which the capabilities have been implemented successfully leading to better performance. The objective is thus to challenge the existing theories in the field of strategic alliances and to qualify them by joining theoretical knowledge about firm level benefits of R&D alliances with theories on individual level work motivation, and behaviors in connection to R&D collaboration. The study is focused on knowledge intensive firms (as distinct from `supplier dominated firms', `specialized equipment suppliers' or `scale intensive firms'). It is stressed that even core knowledge used in the various R&D or innovation processes does not necessarily need to stem from sources internal to the firm, but is likely to originate externally. R&D collaboration has become an important means to foster opportunities to learn, and to access, transfer and utilize knowledge to create innovative solutions But very high failure rates are shown and between fifty and seventy percent of all alliances do not justify the expectations. This vindicates a better understanding of collaborative R&D capabilities. A study of the micro-foundations of these capabilities is both timely and warranted.
hdl:10398/7925
Keywords: 650